Computer Aided Roof Tile Restoration Software Development Using Monte Carlo Method - Jinuntuya, Pinyo (Journal of Architectural/Planning Research and Studies (JARS), 2005)
Computer aided design software on roof tile restoration of historical architecture in this decade are applied only in feature of presentation like 3D modelling, and rendering. But for architectural conservation design process, architects spend much time for pattern design, and color combination from old and new tiles. This roof tile restoration software development tried to apply Monte Carlo Method into core program to make new feature different from traditional CAD software for architects in natural mixed colors pattern design. The user interface of this software use common human-computer interaction by mouse click to make architects just only input ratio of mixed colors, then software will automatically places different old and new colors of roof tile to roof panel just in 1 click, and can display installed roof tile panel in both 2D and 3D view. This object oriented programming based software using C++ Language, OpenGL Graphic Library, and Qt User Interface Library is very flexible to make advanced combination that composed by more than 2 colors in any proportions, and convenience to add more features on calculations.